The Writing Subject and the Constructed Subject in the Poetry of Serbian Women Writers Published after 1970 (Knjiženstvo, journal for studies in literature, gender and culture, 2023)
This paper points to the ways in which female writing subject and female lyrical I are constructed in poetry. The field of poetry was initially constructed as a field of masculine self-expression. The question is how the female subject enters this field and constructs the lyrical I, and how this construction undergoes changes in history. The paper claims that women poets almost always appear within the male dominated poetry formations. Bearing this in mind, the paper points to the way in which women poets enter the field of Serbian poetry in the 1970s, and construct or deconstruct their lyrical I within the stylistic formations of veristic/critical poetry and Vojvodina’s experimental poetry. In addition, the paper explores the formation of the first female poems during the 1990s, as well as contemporary hybrid poems.
Keywords: female poetry; feminism; lyrical I; writing subject